Clinical Predictors of Response to Anti-PD-1 First-Line Treatment in a Single-Centre Patient Cohort: A Real-World Study. Issue 1 (January 2022) - Di Pietro, F.R.; Verkhovskaia, S.; Mastroeni, S.; Carbone, M.L.; Abeni, D.; Di Rocco, C.Z.; Samà, N.; Zappalà, A.R.; Marchetti, P.; De Galitiis, F.; Failla, C.M.; Fortes, C.
Abstract: Aims: Cutaneous melanoma is one of the most immunogenic tumours. Immunotherapy with checkpoint inhibitors, such as anti-PD-1 antibodies, has significantly improved the prognosis in metastatic melanoma. However, only half of the patients respond to this therapy and have a favourable outcome. Identifying factors associated with treatment failure and early identification of responders are both important to select the best treatment approach for each patient. The aim of our study was to investigate clinical biomarkers of response to treatment with anti-PD-1 antibodies. Materials and methods: We selected all patients with stage IV melanoma (n = 147), subjected to first-line treatment with anti-PD-1 in the last 10 years. We investigated the associations between patients' different clinical features and progression-free survival, using the Cox proportional hazards models. Results: In the multivariate analysis, an increased risk of disease progression was observed among patients with stage M1d metastases (hazard ratio 3.30; 95% confidence interval 1.58–6.91), compared with patients with stage M1a-M1b. Moreover, the risk of progression was greater in patients with the Eastern Cooperative Oncology Group Performance Status (ECOG PS) 1 (hazard ratio 2.04; 95% confidence interval 1.02–4.06) and in patients with ECOG PS ≥ 2 (hazard ratio 2.19; 95% confidence interval 1.05–4.55) compared with ECOG PS 0. High levels of lactate dehydrogenase (hazard ratio 2.06; 95% confidence interval 1.18–3.59) and the presence of respiratory diseases (hazard ratio 4.14; 95% confidence interval 1.42–12.0) at the beginning of anti-PD-1 treatment were also associated with an increased risk of disease progression. In a subgroup analysis, neutrophil count and neutrophil/lymphocyte ratio before anti-PD-1 treatment were higher in patients who underwent disease progression. Conclusion: In our study population, independent predictors of disease progression among patients treated with first-line anti-PD-1 were as follows: ECOG PS, staging, lactate dehydrogenase and the presence of respiratory diseases. Highlights: Only half of metastatic melanoma patients respond to checkpoint inhibitor therapy and have a favourable outcome. Investigating clinical biomarkers of response to treatment with anti-PD-1 antibodies, we identified four independent predictors of progression. Independent predictors of disease progression among these patients were ECOG PS, staging, high levels of LDH and the presence of respiratory diseases.